The association of modifiable mechanical ventilation settings, blood gas changes and survival on extracorporeal membrane oxygenation for cardiac arrest. (May 2022) - Tonna, Joseph E.; Selzman, Craig H.; Bartos, Jason A.; Presson, Angela P.; Ou, Zhining; Jo, Yeonjung; Becker, Lance B.; Youngquist, Scott T.; Thiagarajan, Ravi R.; Austin Johnson, M.; Cho, Sung-Min; Rycus, Peter; et al.
Abstract: Research question: Given the relative independence of ventilator settings from gas exchange and plasticity of blood gas values during extracorporeal cardiopulmonary resuscitation (ECPR), do mechanical ventilation parameters and blood gas values influence survival? Methods: Observational cohort study of 7488 adult patients with ECPR from the Extracorporeal Life Support Organization (ELSO) Registry. We performed case-mix adjustment for severity of illness and patient type using generalized estimating equation logistic regression to determine factors associated with hospital survival accounting for clustering by center, standardizing variables by 1 standard deviation (SD) of their values. We examined non-linear relationships between ventilatory and blood gas values with hospital survival. Results: Hospital survival was decreased with higher PaO2 on ECMO (OR 0.69, per 1SD increase [95% CI 0.64, 0.74]; p < 0.001) and with any relative changes in PaCO2 (pre-arrest to on-ECMO) in a non-linear fashion. Survival was worsened with any peak inspiratory pressure >20 cmH2 0 (OR 0.69, per 1SD [0.64, 0.75]; p < 0.001) and above 40% fraction of inspired oxygen (OR 0.75, per 1SD [0.69, 0.82]; p < 0.001), and with higher dynamic driving pressure (OR 0.72, per 1 SD increase [0.65, 0.79]; <0.001). Ventilation settings and blood gas values varied widely across hospitals, but were not associated with annual hospital ECPR case volume. Conclusion: Lower ventilatory pressures, avoidance of hyperoxia, and relatively unchanged CO2 (pre- to on-ECMO) were all associated with survival in patients after ECPR, yet varied across hospitals. Our findings represent potential targets for prospective trials for this rapidly growing therapy to test if these associations have causality.